Analysis of precipitation concentration degree changes and its spatial evolution in the western plain of Jilin Province - RUI , ZHANG; AOQI , LI; TAOTAO , CHEN; GUIMIN , XIA; QI , WU; DAOCAI , CHI (MAUSAM, 2020)
In order to study temporal and spatial evolution of the precipitation concentration degree and period in Western Plains of Jilin during the crop growing season and then adjust irrigation strategy, this paper studied the spatial and temporal characteristics of precipitation. Results are as follows: In the growing season from nearly 35 years, the decrease of precipitation during the growing season contributed more to the reduction of interannual precipitation. The maximum precipitation and precipitation duration showed a slight downward trend whereas the minimum precipitation was reversed. Precipitation duration gradually increased from west to east. In the past 35 years, the precipitation concentration degree (PCD) decreased by linear function of “y = -0.0018x + 0.4655”, indicating that the precipitation exhibited a trend of balanced distribution. The PCD decreased from the northwest to the southeast. From the precipitation concentration period (PCP), it changed from early July to late July. In summary, it was important to strengthen the staged drought-preparedness contingency plans in the region.